Factors affecting spiritual needs in patients with diabetic foot ulcers - Adelina Vidya Ardiyati (Universitas Muhammadiyah Magelang, 2022)
Diabetic foot ulcers are one of the chronic complications of diabetes, leading to disease complexity. As a result, DFU may provoke problems in fulfilling spiritual needs that affect the healing process. This study aimed to analyze the factors related to the spiritual needs of diabetic ulcer patients in Indonesia. This cross-sectional study was conducted on 104 diabetic foot ulcers patient. The patients were recruited from 5 cities in Indonesia using a purposive sampling method from June until August 2022. The instruments consisted of a sociodemographic characteristics form and the Spiritual Needs Questionnaire (SpNQ) to explore patients' Spiritual needs. Then, bivariate and multivariate binary logistics were performed. There is a significant relationship between spiritual needs and age, marital status, length of the wound, and degree of diabetic ulcer (p < 0.05). It is recommended that healthcare workers need to pay attention to the factors that influence the spiritual needs of diabetic foot ulcer patients. Keywords: Diabetic foot ulcer; spiritual needs; community nursing; chronic illness; diabetes care